Tuning the properties of magnetic thin films by interaction with periodic nanostructures - Wiedwald, Ulf; Haering, Felix; Nau, Stefan; Schulze, Carsten; Schletter, Herbert; Makarov, Denys; Plettl, Alfred; Kuepper, Karsten; Albrecht, Manfred; Boneberg, Johannes; Ziemann, Paul (Beilstein Journal of Nanotechnology, 2012)
The most important limitation for a significant increase of the areal storage density in magnetic recording is the superparamagnetic effect. Below a critical grain size of the used CoCrPt exchange-decoupled granular films the information cannot be stored for a reasonable time (typically ten years) due to thermal fluctuations arbitrary flipping of the magnetization direction. An alternative approach that may provide higher storage densities is the use of so-called percolated media, in which defect structures are imprinted in an exchange-coupled magnetic film. Such percolated magnetic films are investigated in the present work. We employ preparation routes that are based on (i) self-assembly of Au nanoparticles and (ii) homogeneous size-reduction of self-assembled polystyrene particles. On such non-close-packed nanostructures thin Fe films or Co/Pt multilayers are grown with in-plane and out-of-plane easy axis of magnetization. The impact of the particles on the magnetic switching behavior is measured by both integral magnetometry and magnetic microscopy techniques. We observe enhanced coercive fields while the switching field distribution is broadened compared to thin-film reference samples. It appears possible to tailor the magnetic domain sizes down to the width of an unperturbed domain wall in a continuous film, and moreover, we observe pinning and nucleation at or close to the imprinted defect structures.
Keywords: colloidal lithography; magnetic data storage; magnetic nanostructures; percolated films

(untitled) - Ishio, S.; Wasiya, T.; Saito, H.; Bai, J.; Pei, W. (J. Appl. Phys., 2006)

(untitled) - Granz, S. D.; Barmak, K.; Kryder, M. H. (J. Appl. Phys., 2012)

(untitled) - Sun, S.; Murray, C. B.; Weller, D.; Folks, L.; Moser, A. (Science, 2000)

(untitled) - Wiedwald, U.; Han, L.; Biskupek, J.; Kaiser, U.; Ziemann, P. (Beilstein J. Nanotechnol., 2010)

(untitled) - Alloyeau, D.; Ricolleau, C.; Langlois, C.; Le Bouar, Y.; Loiseau, A. (Beilstein J. Nanotechnol., 2010)

(untitled) - Dmitrieva, O.; Spasova, M.; Antoniak, C.; Acet, M.; Dumpich, G.; Kästner, J.; Farle, M.; Fauth, K.; Wiedwald, U.; Boyen, H.-G.; Ziemann, P. (Phys. Rev. B, 2007)

(untitled) - Müller, M.; Albe, K. (Beilstein J. Nanotechnol., 2011)

(untitled) - Gruner, M. E.; Entel, P. (Beilstein J. Nanotechnol., 2011)

(untitled) - Wang, J.-P. (Nat. Mater., 2005)

(untitled) - Wang, J.-P.; Shen, W.; Bai, J. (IEEE Trans. Magn., 2005)

(untitled) - McCallum, A. T.; Krone, P.; Springer, F.; Brombacher, C.; Albrecht, M.; Dobisz, E.; Grobis, M.; Weller, D.; Hellwig, O. (Appl. Phys. Lett., 2011)

(untitled) - Suess, D.; Schrefl, T.; Fähler, S.; Kirschner, M.; Hrkac, G.; Dorfbauer, F.; Fidler, J. (Appl. Phys. Lett., 2005)

(untitled) - Tang, Y.; Zhu, J.-G. (IEEE Trans. Magn., 2006)

(untitled) - Suess, D.; Fidler, J.; Porath, K.; Schrefl, T.; Weller, D. (J. Appl. Phys., 2006)

(untitled) - Rahman, T. M.; Lai, C.-H.; Vokoun, D.; Shams, N. N. (IEEE Trans. Magn., 2007)
and references therein

(untitled) - Schulze, C.; Faustini, M.; Lee, J.; Schletter, H.; Lutz, M. U.; Krone, P.; Gass, M.; Sader, K.; Bleloch, A. L.; Hietschold, M.; Fuger, M.; Suess, D.; et al. (Nanotechnology, 2010)
and references therein

(untitled) - Grobis, M.; Schulze, C.; Faustini, M.; Grosso, D.; Hellwig, O.; Makarov, D.; Albrecht, M. (Appl. Phys. Lett., 2011)

(untitled) - Makarov, D.; Krone, P.; Lantiat, D.; Schulze, C.; Liebig, A.; Brombacher, C.; Hietschold, M.; Hermann, S.; Laberty, C.; Grosso, D.; Albrecht, M. (IEEE Trans. Magn., 2009)

(untitled) - Plettl, A.; Enderle, F.; Saitner, M.; Manzke, A.; Pfahler, C.; Wiedemann, S.; Ziemann, P. (Adv. Funct. Mater., 2009)

(untitled) - Gonçalves, M. R.; Makaryan, T.; Enderle, F.; Wiedemann, S.; Plettl, A.; Marti, O.; Ziemann, P. (Beilstein J. Nanotechnol., 2011)

(untitled) - Micheletto, R.; Fukuda, H.; Ohtsu, M. (Langmuir, 1995)

(untitled) - Jiang, P.; McFarland, M. J. (J. Am. Chem. Soc., 2004)

(untitled) - Dimitrov, A. S.; Nagayama, K. (Langmuir, 1996)

(untitled) - Brombacher, C.; Saitner, M.; Pfahler, C.; Plettl, A.; Ziemann, P.; Makarov, D.; Assmann, D.; Siekman, M. H.; Abelmann, L.; Albrecht, M. (Nanotechnology, 2009)

(untitled) - Trautvetter, M.; Wiedwald, U.; Paul, H.; Minkow, A.; Ziemann, P. (Appl. Phys. A, 2011)

(untitled) - Haering, F.; Wiedwald, U.; Häberle, T.; Han, L.; Plettl, A.; Koslowski, B.; Ziemann, P. (Nanotechnology)
submitted for publication

(untitled) - Denkov, N.; Velev, O.; Kralchevsky, P.; Ivanov, I.; Yoshimura, H.; Nagayama, K. (Langmuir, 1992)

(untitled) - Schulze, C.; Schletter, H.; Makarov, D.; McFadzean, S.; Craven, A. J.; Hietschold, M.; Wolff, U.; Neu, V.; Albrecht, M. (Micromaterials and Nanomaterials, 2010)

(untitled) - Raabe, J.; Tzvetkov, G.; Flechsig, U.; Böge, M.; Jaggi, A.; Sarafimov, B.; Vernooij, M. G. C.; Huthwelker, T.; Ade, H.; Kilcoyne, D.; Tyliszczak, T.; Fink, R. H.; et al. (Rev. Sci. Instrum., 2008)

(untitled) - Ulbrich, T. C.; Assmann, D.; Albrecht, M. (J. Appl. Phys., 2008)

(untitled) - Ulbrich, T. C.; Makarov, D.; Hu, G.; Guhr, I. L.; Suess, D.; Schrefl, T.; Albrecht, M. (Phys. Rev. Lett., 2006)

(untitled) - Murillo, R.; Siekman, M. H.; Bolhuis, T.; Abelmann, L.; Lodder, J. C. (Microsyst. Technol., 2007)

(untitled) - Maret, M.; Cadeville, M. C.; Herr, A.; Poinsot, R.; Beaurepaire, E.; Lefebvre, S.; Bessière, M. (J. Magn. Magn. Mater., 1999)

(untitled) - Krone, P.; Makarov, D.; Schrefl, T.; Albrecht, M. (J. Appl. Phys., 2009)

(untitled) - Hellwig, O.; Berger, A.; Thomson, T.; Dobisz, E.; Bandic, Z. Z.; Yang, H.; Kercher, D. S.; Fullerton, E. E. (Appl. Phys. Lett., 2007)

(untitled) - Kondorsky, E. (J. Phys. (Moscow), 1940)

(untitled) - Stoner, E. C.; Wohlfarth, E. P. (Philos. Trans. R. Soc. London, Ser. A, 1948)

(untitled) - Ulbrich, T. C.; Bran, C.; Makarov, D.; Hellwig, O.; Risner-Jamtgaard, J. D.; Yaney, D.; Rohrmann, H.; Neu, V.; Albrecht, M. (Phys. Rev. B, 2010)